Missing trial results: analysis of the current publication rate of studies in pediatric dialysis from 2003 to 2020 - Patry, Christian; Fichtner, Alexander; Höcker, Britta; Ries, Markus; Schmitt, Claus P.; Tönshoff, Burkhard (Pediatric nephrology, 2023)
BACKGROUND: Decision-making in the field of pediatric dialysis requires evidence from clinical trials, but, similar to other fields of pediatric medicine, might be affected by a low trial publication rate. - METHODS: We analyzed the current publication rate, the time to publication, and factors that might be associated with both rate of and time to publication in pediatric dialysis studies registered as completed on ClinicalTrials.gov from 2003 until November 2020. - RESULTS: Fifty-three respective studies were identified. These enrolled 7287 patients in total. 28 of 53 studies (52.8%) had results available. We identified a median time to publication of 20.5 months (range, 3-67). Studies published after the FDA Amendments Act establishment in 2007 were published faster (P = 0.025). There was no trend toward a higher publication rate of studies completed more recently (P = 0.431). 26 of 53 studies (49.1%) focused on medication and control of secondary complications of kidney failure. 12 of 53 studies (22.6%) enrolled only children, were published faster (P = 0.029) and had a higher 5-year publication rate (P = 0.038) than studies enrolling both children and adults. 25 of 53 studies (47.1%) were co-funded by industry. These were published faster (P = 0.025). - CONCLUSIONS: Currently, only 52.8% of all investigated studies in pediatric dialysis have available results, and the overall median time to publication did not meet FDA requirements. This might introduce a publication bias into the field, and it might negatively impact clinical decision-making in this critical subspecialty of pediatric medicine. A higher resolution version of the Graphical abstract is available as Supplementary information.